Hubungan kecerdasan emosional dengan kemampuan pemecahan masalah matematis peserta didik di Sekolah Dasar - Dhea Puspita Kusmandari; Fitri Aida Sari; Sukriadi Sukriadi; Fara Virgianita Pangadongan; Wa Pain (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2026)
Mathematical problem-solving skills are an important aspect of mathematics education and are influenced by various factors, including emotional intelligence. This study examined the relationship between emotional intelligence and mathematical problem-solving skills among elementary school students. This study employed a quantitative correlational design. The participants consisted of 26 fifth-grade elementary school students. Data were collected using an emotional intelligence questionnaire and a mathematical problem-solving test, and analyzed using the Spearman rank correlation test. The results showed a positive correlation between emotional intelligence and mathematical problem-solving skills; however, the relationship was not statistically significant. This may be attributed to the small sample size, the relatively homogeneous distribution of test scores, and the uniform learning environment. These findings suggest that emotional intelligence is not the sole factor influencing students' mathematical problem-solving skills. Other contributing factors include cognitive abilities, learning motivation, student engagement, teachers' roles, instructional strategies, and family support